An Interpretation of 2 Kings 5:1-19 and Its Lessons for the Church in Nigeria - Ogunkunle, C. O. (KWASU Journal of Religious Studies, 2018)
Living in good health is a legitimate concern of human beings from time immemorial. The Yoruba of South West Nigeria has a popular saying that Ilera l'oro which literally means health is wealth. However, the prevalence of various diseases and sicknesses in Nigeria is a threat to good living. Therefore, this paper examines 2 Kings 5:1-19 with reference to Naaman, a respected commander of the Israelite army, who had a serious skin disease. A historical-exegetical method is utilized. The exegesis revealed that absolute faith in God is required for healing, and that the use of means such as water is allowed for healing process. The paper postulates that the Church in Nigeria should educate her members to be conscious of various diseases and sicknesses in the society and seek for appropriate medical or spiritual assistance.